MEDU-34. PILOT STUDY OF A SURGERY AND CHEMOTHERAPY-ONLY APPROACH IN THE UPFRONT THERAPY OF CHILDREN WITH WNT-POSITIVE STANDARD RISK MEDULLOBLASTOMA. (23rd April 2019) - Cohen, Kenneth; Bandopadhayay, Pratiti; Chi, Susan; London, Wendy; Rodriguez, Fausto; Hawkins, Cynthia; Yang, Edward; Aguilera, Dolly; Castellino, Robert; MacDonald, Tobey; Stapleton, Stacie; Ashley, David
Abstract: BACKGROUND: Molecular subclassification of medulloblastoma identifies Wnt-positive medulloblastoma (WPM) as a highly favorable subtype with event-free survival (EFS) exceeding 90% when treating patients following near total or complete resection with standard dose craniospinal irradiation and boost radiation to the posterior fossa (XRT) followed by adjuvant chemotherapy. This pilot study explored the safety of omitting XRT in children with standard-risk WPM. METHODS: Subjects had to meet usual standard-risk criteria (< 1.5 cm2 residual tumor, no metastatic spread, no anaplasia) and have a WPM. Initial criteria for determination of WPM included nuclear beta-catenin immunopositivity, monosomy 6 and absence of myc-amplification by FISH. Following the first two subject enrollments, criteria for WPM was revised to no longer require nuclear beta-catenin immunopositivity, and substituted gene-expression profiling by Nanostring. Upon consent, eligible subjects received adjuvant chemotherapy following the Children's Oncology Group ACNS0331 AAB-AAB-AAB (A=cisplatin/CCNU/VCR; B=cyclophosphamide/vincristine) backbone and followed for EFS. RESULTS: Fourteen children underwent prescreening of which six children who met molecular criteria for WPM elected to enroll on study treatment. Subject #1 completed planned protocol therapy, requiring a 50% reduction in cisplatin for most of therapy for ototoxicity, but relapsed 3 months following the completion of therapy. Subject #2 completed planned protocol therapy without dose reductions or delays, but relapsed 6 months following the completion of therapy. In both cases, relapse was local and disseminated. Following the second relapse, further accrual was halted. Of the remaining 4 subjects, two have recently completed protocol therapy and remain free of disease. The final two subjects are in the midst of protocol therapy. Additional therapy in the form of XRT and/or chemotherapy dose intensification has been recommended to these remaining 4 subjects. CONCLUSIONS: Chemotherapy following ACNS0331, in the absence of XRT, appears to be insufficient for the treatment of non-metastatic WPM.